Quality Gap in Family Planning Service in Health Care Centers of Shahid Beheshti University of Medical sciences. - Ghanbari, Shahla; Ramezankhani, Ali; Mohammadi, Gohar; Keyhan, Mohammad Reza; Mehrabi, Yadollah (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Family planning services are frequently used and important services for women of reproductive age. These services are crucial in enabling women to meet their fertility goals. Materials and methods : In a cross-sectional study, the exception s and perceptions of women who seeking care from health care center under the supervision of the Shahid Beheshti University of Medical Sciences regarding family planning services were investigated using revised SERVQUAL questionnaire. Overall quality of service, satisfaction and willingness to come again also were measured as response variables. Findings: The mean age of sample was . years (SD= . ). . had at least years of education and . were employed. . of participants visited the health centers at least times. There was an overall negative gap score of - . between clients’ expectations and perceptions in all dimensions of service quality (p< . ), showing that customer expectations of family planning services were not met. The mean score of quality of service, satisfaction and willingness to come again were . , . , and . of respectively. Conclusion: This study showed that patients were relatively satisfied by the quality of the family planning services provided by health care centers, although the system’s performance fell short of their expectations. Planning and implementation of proper intervention in diverse dimension of service quality can lead to clients’ satisfaction and service quality improvement. Keywords: Gap, Service Quality, Family Planning, Satisfaction, Health care center